1999
DOI: 10.1021/bp990062x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Study of the Concentration Dependence of the Mass Transfer Rate Coefficient in Anion-Exchange Chromatography of Bovine Serum Albumin

Abstract: The experimental results of a previous study of the mass transfer kinetics of bovine serum albumin (BSA) in ion-exchange chromatography under nonlinear conditions are reevaluated. The analysis of the concentration dependence of the lumped mass-transfer rate coefficient (k(m,L)) provides information on the kinetics of axial dispersion, fluid-to-particle mass transfer, intraparticle mass transfer, and adsorption/desorption. The new analysis shows that the contribution of intraparticle mass transfer is the domina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 48 publications
3
23
0
Order By: Relevance
“…The plot of δd resembles that of the reciprocal of km,L (= δtotal). It is concluded that the concentration dependence of km,L results mainly from that of Ds because Dp is assumed to be independent of C. This situation is similar to those found in anion exchange 17,18 and reversed-phase chromatography. 27 A similar conclusion is derived from Fig.…”
Section: Explanation Of the Positive Concentration Dependence Of Kmlsupporting
confidence: 72%
See 4 more Smart Citations
“…The plot of δd resembles that of the reciprocal of km,L (= δtotal). It is concluded that the concentration dependence of km,L results mainly from that of Ds because Dp is assumed to be independent of C. This situation is similar to those found in anion exchange 17,18 and reversed-phase chromatography. 27 A similar conclusion is derived from Fig.…”
Section: Explanation Of the Positive Concentration Dependence Of Kmlsupporting
confidence: 72%
“…The values of Ds are between 1 × 10 -8 and 1 × 10 -7 cm 2 s -1 . In previous papers, 17,18,27 we demonstrated a similar positive concentration dependence of Ds in two phase systems, in anion exchange and reversed-phase HPLC. In anion exchange chromatography of BSA, the heterogeneous surface model could represent the positive concentration dependence of Ds.…”
Section: Derivation Of An Estimate Of Dssupporting
confidence: 63%
See 3 more Smart Citations